Полет над миром: [стихи всем странам мира] / Владимир Тяптин - Тяптин Владимир Яковлевич (Проект, 2016)
Экземпляры: ф.6 (20171211) / Инвентарный номер: 49630 / Цена: 80.00 / Сис.шифр: 84(2Рос=Удм) / Авт.знак: Т 99 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Удм)